ENHANCING EFL STUDENTS’ SPEAKING SKILLS AND ENGAGEMENT THROUGH TURN-TAKING STRATEGIES - Gaffar, Muhammad Andriana; Rismayanti, Rismayanti; Ilmi, Hapidotul; Nuryani, Siti (English Review: Journal of English Education, 2025)
English communication skills are one of the 21st century educational skills demand to face the technological and industrial era. The previous studies have examined the influence of Turn-Taking Strategy (TTS) on speaking skill in the classroom, but no one has examined its influence on the issue of student engagement which is always being discussed recently. Hence, this study addresses the gap by investigating the effect of TTS through speaking skills and student engagement in EFL classroom. A total of 30 tenth grade students at SMK TPI Al-Ghoniyyah are divided into experimental and control groups using a non-random sampling approach with purposive sampling technique. This study used a quasi-experimental, non-equivalent (pretest and post-test) control group design. The researcher used observation sheet, speaking tests and documentation to collect the data and parametric statistical analysis which consists of testing requirements and hypotheses to analyse the data. The findings indicated that TTS positively influence students' speaking skills and engagement with a significance value of 0.00 ≤ 0.05. The mean difference values of experimental and control group were 3.20 and 18.20 higher than 1.00 and 3.07 showed the impact of TTS in fostering EFL student’s self-confidence, developing interactional competence, and overcoming engagement problems. The formation of positive characters and personality types of EFL student was revealed indirectly in this study.